Correlation Between Gut Microbiota and Testosterone in Male Patients With Type 2 Diabetes Mellitus - Liu, Shuang; Cao, Ruying; Liu, Luna; Lv, Youyuan; Qi, Xiangyu; Yuan, Zhongshang; Fan, Xiude; Yu, Chunxiao; Guan, Qingbo (Frontiers in Endocrinology, 2022)
Objective: This study aimed to investigate the association between testosterone level and gut microbiota in male patients with type 2 diabetes mellitus (T2DM), and to provide a new strategy to elucidate the pathological mechanism of testosterone deficiency in T2DM patients. Methods: In an observational study including 46 T2DM male patients, the peripheral venous blood and fecal samples of all subjects were collected. The V3-V4 region of bacterial 16 S rDNA was amplified and sequenced. Alpha and Beta diversity were calculated by QIIME software. The possible association between gut microbial community and clinical indicators was assessed using the Spearman correlation coefficient. The association between the relative abundance of bacteria and testosterone levels was discovered using linear regression analysis in R language. Results: There was no substantial difference in alpha and beta diversity. Blautia and Lachnospirales were significantly much higher in the testosterone deficiency group. Linear regression analysis showed that the abundance of Firmicutes at phylum level and Lachnospirales at order level were negatively correlated with testosterone level. After corrected for C-reactive protein (CRP) and homeostatic model assessment of insulin resistance (HOMA-IR), the relative abundance of Lachnospirales still had a significant negative correlation with testosterone level. Meanwhile, at the genus level, Lachnoclostridium, Blautia, and Bergeyella had a statistically significant negative association with testosterone level, respectively. Blautia was positively associated with FPG and total cholesterol level. Streptococcus was found positively associated with insulin, connecting peptide and index of homeostatic model assessment of insulin resistance. Conclusion: T2DM patients with testosterone deficiency have different gut microbiota compositions compared with T2DM patients alone. Low serum testosterone patients tend to have an increased abundance of opportunistic pathogens, which may be related to the occurrence and development of testosterone deficiency.